2013
DOI: 10.1111/jonm.12104
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing home care nurse intention to remain employed

Abstract: Home care nursing management should support nurse autonomy, allow flexible scheduling, promote reasonable workloads and create opportunities for team building that strengthen supportive relationships among home care nurses and other health team members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
109
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(134 citation statements)
references
References 23 publications
(91 reference statements)
12
109
2
2
Order By: Relevance
“…At the beginning of 2020, the use of nurses’ professional competence in relation to vulnerability in health on a global scale and forming nursing competence in international work has dominated the Global Nursing arena (Brunetto, Farr‐Wharton, & Shacklock, 2012; Gutierrez, Candela, & Carver, 2012; Lesia & Roets, 2013; Squires & Juárez, 2012; Toren, Zelker, & Porat, 2012; Walton‐Roberts, 2012; Zhou, Windsor, Theobald, & Coyer, 2011; Zinsli & Smythe, 2009). Finally, in the mid‐2020s, the question of global leadership, nursing faculty competence, and discussions on nurse professionals and nurse faculty retirement has been key issues (Havens, Warshawsky, & Vasey, 2013; Meum, Ellingsen, Monteiro, Wangensteen, & Igesund, 2013; Tourangeau et al.,2014). During recent years, the vulnerability of nurse professionals’ educational and work status has been addressed (Ortiga, 2014; Weng, Huang, Chen, & Chang, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the beginning of 2020, the use of nurses’ professional competence in relation to vulnerability in health on a global scale and forming nursing competence in international work has dominated the Global Nursing arena (Brunetto, Farr‐Wharton, & Shacklock, 2012; Gutierrez, Candela, & Carver, 2012; Lesia & Roets, 2013; Squires & Juárez, 2012; Toren, Zelker, & Porat, 2012; Walton‐Roberts, 2012; Zhou, Windsor, Theobald, & Coyer, 2011; Zinsli & Smythe, 2009). Finally, in the mid‐2020s, the question of global leadership, nursing faculty competence, and discussions on nurse professionals and nurse faculty retirement has been key issues (Havens, Warshawsky, & Vasey, 2013; Meum, Ellingsen, Monteiro, Wangensteen, & Igesund, 2013; Tourangeau et al.,2014). During recent years, the vulnerability of nurse professionals’ educational and work status has been addressed (Ortiga, 2014; Weng, Huang, Chen, & Chang, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the articles, Global Nursing practice in dynamic working environments was influenced by predictors such as encouragement in the work place; an organizational culture that values diversity and an inclusive social atmosphere (Garner et al., 2008; Gerrish & Griffith, 2003; Harrowing et al., 2010; Havens et al., 2013; Kim et al., 2006; Toren et al., 2012; Tourangeau et al., 2014; Weng et al., 2015). Nurse professionals’ equal opportunities for professional practice, use of competence and collaboration in academic and practice contexts were described as essential in supportive environments (Garner et al., 2008; Gerrish & Griffith, 2003; Harrowing et al., 2010; Wros et al., 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning job resources, previous studies have identified support from superiors or colleagues, feedback, and job autonomy, as important. Among them, job autonomy is known to be a predictor of work engagement [22] , and this has been shown among nurses [23,24] and home visiting nurses [25] . By being given autonomy when nurses are providing end-of-life care, nurses might engage more in end-of-life care.…”
Section: Autonomy Of Providing End-of-life Care and Attendance At Endmentioning
confidence: 99%